The biting performance of Homo sapiens and Homo heidelbergensis. Issue 118 (May 2018) - Godinho, Ricardo Miguel; Fitton, Laura C.; Toro-Ibacache, Viviana; Stringer, Chris B.; Lacruz, Rodrigo S.; Bromage, Timothy G.; O'Higgins, Paul
Abstract: Modern humans have smaller faces relative to Middle and Late Pleistocene members of the genus Homo . While facial reduction and differences in shape have been shown to increase biting efficiency in Homo sapiens relative to these hominins, facial size reduction has also been said to decrease our ability to resist masticatory loads. This study compares crania of Homo heidelbergensis and H. sapiens with respect to mechanical advantages of masticatory muscles, force production efficiency, strains experienced by the cranium and modes of deformation during simulated biting. Analyses utilize X-ray computed tomography (CT) scan-based 3D models of a recent modern human and two H. heidelbergensis . While having muscles of similar cross-sectional area to H. heidelbergensis, our results confirm that the modern human masticatory system is more efficient at converting muscle forces into bite forces. Thus, it can produce higher bite forces than Broken Hill for equal muscle input forces. This difference is the result of alterations in relative in and out-lever arm lengths associated with well-known differences in midfacial prognathism. Apparently at odds with this increased efficiency is the finding that the modern human cranium deforms more, resulting in greater strain magnitudes than Broken Hill when biting at the equivalent tooth. Hence, the facial reduction that characterizes modern humans may not have evolved as a result of selection for force production efficiency. These findings provide further evidence for a degree of uncoupling between form and function in the masticatory system of modern humans. This may reflect the impact of food preparation technologies. These data also support previous suggestions that differences in bite force production efficiency can be considered a spandrel, primarily driven by the midfacial reduction in H. sapiens that occurred for other reasons. Midfacial reduction plausibly resulted in a number of other significant changes in morphology, such as the development of a chin, which has itself been the subject of debate as to whether or not it represents a mechanical adaptation or a spandrel.